Can We Reduce Rainfed Maize (Zea mays L.) Nitrogenous Fertilizer Application Rate with Addition of Nitrapyrin?. Issue 4 (21st February 2016) - Chatterjee, A.; Cattanach, N.; Awale, R.; Thapa, R.
ABSTRACT: Application of nitrification inhibitor has potential to increase soil nitrogen (N) retention throughout the growing season and finally increase corn ( Zea mays L.) yield. During the 2012–2014 growing seasons, on-farm field trials were conducted to determine the effects of nitrapyrin (Instinct) with two N sources, urea and urea ammonium nitrate, at two rates, 85% and 100% of recommended N, and side-dress on grain yield and soil inorganic N availability in the Red River Valley of the North Dakota. Preplant urea N at 100% recorded the greatest yield in 2 out of 3 years. At late sampling, the greatest soil inorganic N was observed with side-dress urea ammonium nitrate at 100% within 0–30 cm (last 2 years). For spring fertilizer N management, addition of nitrapyrin had no effect on yield and inconsistent effect on soil N availability. Our results suggest that fertilizer N management should be evaluated on a local scale and consider annual variability in weather.